The Position And Function Of Notary In The Using Of State Symbol - Arief Rahman Siregar; Andhika Widya Kurniawan; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2020)
This study tried to answer the problem formulation is What position and Function of Notary in using the State symbol? What if Notaries do malpractices in the using of State Symbol and how sanctions against malpractice Notary Public who use the State Symbol? The purpose of this study to determine the position and Function of Notary in using the State Symbol, and determine sanctions against notaries who do mal practice in the using of State Symbol.This research was conducted using the normative method, means testing and reviewing secondary data, using literature data in the form of positive law relating to Legislation relating to the issues discussed.The results of this study concluded that a Notary Public in the office using the Symbol State under Article 16 paragraph (1) letter k of Notary law) and use of the State symbol of Notary's Stamp or Head Letter Position as stipulated in Article 54 paragraph (1) letter j Act No. 24 of 2009 and as Stamp of Department Office as stipulated in Article 54 paragraph (2) letter j Act No. 24 of 2009, while the Notary malpractice in the using of State symbol is not necessarily directly given to criminal sanctions as a form of application of the law ultimum remidium. because there are several steps that must be passed given the Notary has its own rules in the Law on Notary. Notary of the behavior is also governed by a special organization that Indonesian Notary Association (INI), but still asked the criminal responsibility under Act No. 24 of 2009 and Article 154 of the Criminal Code letter if indeed Notary proven legally and convincingly to have malpractice against the using of State Symbol.Keywords: Notary Authority; Notary Position; Sanctions Against Notary.